Physicochemical analysis of a gongocomposite in the initial production of crisp lettuce seedlings - Rodrigues Gomes, Amarildo; Buzatt Castilho, Luan; Candido Duarte, Edmilson; Vargas Borges, Elizene; Ribeiro Coutinho, Pablo Wenderson (Scientia Agraria Paranaensis, 2021)
Tree pruning in urban centers generates residues, which can be used as organic composites in the production of crisp lettuce seedlings. Given the above, the aim of this work was to perform a physicochemical analysis of the gongocomposite in the production of crisp lettuce seedlings. The experiment was carried out in a rural property in Reserva do Cabaçal-MT, with a completely randomized design comprising five treatments and five replications. To obtain the substrates, the gongocomposite was made from Trigoniulus corallinus, in the following proportions: 40% of Paspalum notatum (grass) + 30% of the pruning residues of tree species Terminalia catappa, Licania tomentosa, Senna siamea, and Albizia lebbeck composed of leaves, leaflets, and fine branches, dried and crushed, where the process lasted 120 days. Substrates were evaluated regarding physical and chemical properties. At 24 days after sowing, shoot fresh and dry mass, root fresh and dry mass, root volume, seedling vigor, and stability of lettuce clods were measured. The gongocomposite from the grass (Paspalum notatum) + oiti + albizia (40% + 30% pruning residues + 30% pruning residues) presented better physicochemical characteristics and better initial development of lettuce seedlings.